Experimental Study on the Performance of Mechanical Coupler Splice Made of Rebar Under Monotonic Loading - Muhammad, Heidi; Saputra, Ashar; Triwiyono, Andreas (Universitas Muhammadiyah Yogyakarta, 2023)
The lap splice method presents a drawback due to reinforcement congestion, affecting the pouring and evenness of the concrete. Additionally, lap splicing significantly contributes to construction waste. As a result, research was conducted on mechanical connections using reinforcements to reduce construction waste and demonstrate the feasibility of these splices. In this study, the threaded coupler with standard national coarse threads splice method was employed, and tests were conducted following ASTM A1034-10a standards with monotonic tensile loading. Test specimens were created using 13 and 16 mm reinforcement sizes, varying the length and diameter of the coupler, and including welding at the coupler ends. The test results demonstrated that reinforced bars with splices exhibit a stress-strain relationship similar to intact reinforcement. However, these reinforced bars with splices did not meet the requirements outlined in SNI 2052:2017 concerning maximum stress and strain, including their comparison. Therefore, the utilization of these splices is not suitable for critical load-bearing areas.